A Novel Repetition Rate Adjustable SBS-Based Q-Switched Fiber Laser - Shaodong Hou; Zhimu Gu; Ping Chen; Jinyan Li; Luyun Yang; Jinggang Peng; Haiqing Li; Nengli Dai (IEEE Photonics Journal)
We experimentally demonstrated a novel repetition rate adjustable SBS-based Q-switched fiber laser. An inserted Fabry-Perot interferometer formed by two non-contact end faces of two FC/PC fiber connectors was inserted to help the system stabilize the random output of SBS-based Q-switching. By mechanically fine-tuning the length of the inserted Fabry-Perot interferometer, a linear and continuous repetition rate adjustment under a fixed pump power was achieved. This method paves a new way for the indirect control of repetition rate in SBS-based Q-switched fiber lasers. It is also found out that higher pump power allows wider adjustment range. At 600 mW pumping which is highest pump power of the source, the repetition rate almost tripled from 11.22 kHz to 32.06 kHz only by varying the length of FP cavity in less than 3 μm. In the meantime, the variation of pulse width, output power and single pulse energy were recorded and analyzed under different fixed pump powers. Although the adjusting range of repetition rate is not very wide but the tuning of repetition rate due to such a small length changing is unique and valuable. This original repetition rate control technique has great potential in areas like environment sensing and material detections.